Damga vergisinde konu - Ateş, Leyla (My University, 2002)
DAMGA VERGİSİNDE KONU Damga vergisi kişilerin kendi aralarında ya da devletle, ticari veya medeni alanda yaptıkları hukuki işlemler nedeniyle düzenledikleri kağıtlar dolayısıyla alınır. Öyleyse, damga vergisinde konu kağıtlardır. Çalışmamızın birinci bölümünde damga vergisinde vergi konusunun hukuki çerçevesi ortaya konulmuştur. Birinci alt başlıkta kavram ve kapsam belirlenmiştir. Damga vergisine ilişkin mevzuatımızdaki temel düzenleme olan 488 sayılı Damga Vergisi Kanunu 1. maddesinin 1. fıkrasıyla kağıdı, 2. maddesiyle de kağıt benzeri mektup ve şerhi vergi konusu olarak belirlemiş ve kağıdı tanımlama yoluna gitmiştir(DVK.m.1/ 2). Kağıt benzerlerinin vergilendirilmesi ise kağıt mahiyetinde olmasının yanında bazı şartlara bağlanmıştır. İkinci alt başlıkta, damga vergisinde vergilendirme yetkisinin kapsamı açıklanmıştır. Damga vergisine tabi olabilmeleri için vergi konusu kağıtların ya düzenleme yeri Türkiye olacak ya da düzenleme yeri yurt dışında veya Türkiye'deki yabancı elçilik ve konsolosluklarda olmakla birlikte ibraz yeri, devir yeri veya faydalanma yeri Türkiye olacaktır(DVK.m.1/ 3). Damga vergisine konu kağıtların vergilendirilmeye ilişkin bir takım hukuki sonuçları vardır. Üçüncü alt başlıkta bunlar belirlenmiştir. Bunlardan birincisi, kağıdın temelinde yer alan hukuki işlemin unsurlarındaki eksikliğin işlemi hükümsüz kılması ve yapılan vergilendirmeyi sebepsiz bırakmasıdır. İkincisi, vergisi zamanaşımına uğrayan kağıdın hükmünden tahakkuk zamanaşımından sonra yararlanıldığı takdirde vergi alacağının yeniden doğmasıdır. Üçüncüsü ise, vergi konusu kağıdın birden fazla işlem içerecek şekilde düzenlendiği veya düzenleme birden çok nüsha olarak yapıldığında alınacak vergi tutarını etkileyen sonuçların meydana gelmesidir. Dördüncü alt başlıkta ise damga vergisine konu kağıtların nitelendirilmesi ele alınmıştır. DVK.m.4'te nitelendirmeye ilişkin kurallar getirilmiştir. Çalışmamızın ikinci bölümünde damga vergisinde kağıt türleri incelenmiştir. Birinci alt başlıkta Kanuna ekli (1) sayılı tabloda yazılı olan, vergi konusuna giren kağıtlar, ikinci alt başlıkta ise Kanuna ekli (2) sayılı tabloda ve özel kanunlarda vergiden istisna edilen kağıtlar sayılmıştır. Sonuç bölümünde, her vatandaşın düzenleyebileceği kağıtların sayıldığı (1) sayılı tablonun günümüz işlemlerini kapsamadığı için yetersiz kaldığı ve elektronik ticaretin gelişmesine paralel olarak kağıtsız düzenlenen işlem sayısındaki artışın vergi konusunu daralttığı tespit edilmiştir. Bu daralmaya kanun koyucunun getirdiği istisnaların katkısı vurgulanmıştır. THE SUBJECT IN STAMP DUTY The Stamp Duty is taken through the printed matters, which people make out because of the judicial processes in commercial or civil areas among themselves or with the state. So the subject in Stamp Duty is printed matters. At the first part of the essay the judicial scale of the subject of tax in Stamp Duty had been designated. At first subheading the concept and extent had been determined. 488 numbered Stamp Duty Law (SDL), which is the basic regulation in our legislation about Stamp Duty, has chosen to define printed matter and determined; the printed matter in first clause of the first article, and command and letter similar to printed matter in second article (SDL. article1/ 2). Taxation of printed matter alike has been tied to some circumstances besides their being of printed matters. At second subheading the extent of authorization to tax in stamp duty had been explained. To be included in Stamp Duty, tax subjected printed matters should either have Turkey as location of preparation or have Turkey as location of presentation, transfer or exploitation although they might be prepared at foreign embassies and consulships in Turkey or abroad. Printed matters subjected to Stamp Duty have some judicial results related to taxation. These had been determined at third subheading. The first of these results is the invalidation of the process by defect in elements of judicial process at the basis of printed matter and leaving of the taxation done without a cause. The second is the rebirth of the tax debt when utilization of judgment of printed matter tax had done after the accrual lapse of time. The third one is the taking place of the results affecting the tax amount to be taken when printed matter subjected to tax is prepared to include processes more than one or when the preparation is done as more than one copy. At the fourth subheading the qualification of printed matters subjected to Stamp Duty had been studied. In article 4 of SDL rules about qualification had been set. At the second part of this study kinds of printed matters in Stamp Duty had been examined. At first subheading printed matters which are included by subject of tax and written on the table numbered (1) attached to the law, at second subheading printed matters which are included on table numbered (2) attached to the law, and which are free from tax in special articles had been counted. At conclusion it had been established that; the table numbered (1), at which the printed matters everybody is able to prepare are counted, is insufficient as it does not contain current processes, and the increase in the number of processes prepared without paper parallel to the improvement in electronic-commerce tightens the subject of tax. The contribution of exceptions set by legislative to this tightening had been mentioned.
Keywords: Vergi Hukuku-Türkiye